Serial Image Learning Media to Improve Fourth Grade Elementary School Students' Narrative Writing Skills - Wijayasir, Urie Elmara; Astuti, Tri (LPPM Undiksha, 2025)
Many children still have difficulty developing their creative ideas through effective writing and sentences. This study aims to develop a series of picture learning media that can improve students' narrative writing skills. This study uses the Research and Development method with the ADDIE model. The subjects of the study were 29 fourth-grade students. Validation of the series of picture-learning media was carried out by one media expert and one material expert. Data collection methods used in this study include observation, interviews, tests, questionnaires and documentation. The instruments used in collecting data were questionnaire sheets and test questions. The techniques used in analyzing data were qualitative, quantitative, and inferential statistical descriptive analysis. This study's results indicate that using a series of picture media is quite effective in improving students' writing skills. This is indicated by the results of the small group N-gain score of 0.6349 and the N-gain results of 0.6191. The results of the media expert validation obtained 93.75% with the category